Active referral plus a small financial incentive upon cessation services use on smoking abstinence: a community-based, cluster-randomised controlled trial - Xue Weng, PhD; Yongda Wu, PhD; Tzu Tsun Luk, PhD; William Ho Cheung Li, PhD; Derek Yee Tak Cheung, PhD; Henry Sau Chai Tong, BBA; Vienna Lai, MPH; Tai Hing Lam, MD; Man Ping Wang, PhD (Elsevier, 2021)
Summary: Background: Many smokers do not use existing free or low-cost smoking cessation services, cost-effective interventions to increase use are needed. Methods: We did a 2-armed cluster randomised controlled trial (cRCT) in Hong Kong, China, to evaluate the effectiveness of active referral plus a small financial incentive on abstinence. Chinese adult smokers who smoked at least 1 cigarette per day were proactively recruited from 70 community sites (clusters). Random allocation was concealed until the recruitment started. The intervention group received an offer of active referral to cessation services at baseline plus an incentive (HK$300/US$38) after using any cessation services within 3 months. The control group received general brief cessation advice. The primary outcomes were biochemically validated abstinence at 3 and 6 months. Operating costs in real-world implementation was calculated. Trial Registry: ClinicalTrials.gov NCT03565796. Findings: Between June and September 2018, 1093 participants were randomly assigned to the intervention (n=563) and control (n=530) groups. By intention-to-treat, the intervention group showed higher validated abstinence than the control group at 3 months (8.4% vs. 4.5%, risk ratio [RR] 1.88, 95% CI 1.01-3.51, P=0.046) and 6 months (7.5% vs. 4.5%, RR 1.72, 95% CI 1.01-2.93, P=0.046). Average cost per validated abstinence was lower in the intervention (US$ 421) than control (US$ 548) group. Interpretation: This cRCT has first shown that a simple, brief, and low-cost intervention with active referral plus a small monetary incentive was effective in increasing smoking abstinence and smoking cessation service use in community smokers. Funding: Hong Kong Council on Smoking and Health.